A HOLISTIC EVALUATION OF MANAGEMENT GRADUATES' DETERMINATION TO BECOME ENTREPRENEURS IN TODAY'S BUSINESS ENVIRONMENT - Varalakshmi, Ch. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
India has a higher rate of unemployment due to its large population, high inflation rate, and a lack of entrepreneurs. There are more job searchers than job creators. More job creators are needed in India. This dynamic business climate is providing new opportunities and sectors. Because of the pandemic Covid-19, massive technological intervention in every area resulted in new business patterns. We, too, have many sources of funding for an entrepreneurial venture. Even the government intends to promote fresh inventive ideas, incubation centers, and start-ups. The most significant barriers are a lack of understanding about funding options and central government entrepreneurial efforts. Even young people must come up with business concepts in order to launch their own ventures. They must develop their self-employment skills. This study is an attempt to examine the students' perceptions and degree of interest in pursuing entrepreneurship as a career. Various aspects, such as their demographics and employment aspirations, were considered for the study. This study included around 200 students from different education levels.